Implementing Structured Strength Training for Muscle Endurance in Satchel Peace Softball Athletes - Alvent Bayu Permana Inggaswana; Cahyo Yuwono (Universitas Negeri Semarang, 2026)
This research investigated the effectiveness of a structured strength training program in enhancing the muscular endurance of female softball athletes from Satchel Peace Cirebon. A quantitative experimental approach was employed using a One-Group Pretest–Posttest Design, involving 23 athletes selected through total sampling. Muscular endurance was evaluated before and after the intervention using one-minute push-up and sit-up tests. The training intervention consisted of 10 sessions designed according to the principles of progressive overload, goal-oriented training, and recovery. Statistical analysis was conducted with IBM SPSS and included the Shapiro–Wilk normality test, Levene's homogeneity test, and a paired-sample t-test. The findings demonstrated an increase in the mean score from 24.91 during the pretest to 32.96 in the posttest. Furthermore, the paired-sample t-test produced a p-value of 0.000 (< 0.05), indicating the rejection of H₀ and acceptance of H₁. These results confirm that a structured strength training program significantly improves the muscular endurance of softball athletes. The observed improvement may be attributed to neuromuscular adaptations and enhanced muscle function resulting from consistent and continuous training.